2012
DOI: 10.1080/00207594.2011.645482
|View full text |Cite
|
Sign up to set email alerts
|

Resemblance and investment in children

Abstract: According to evolutionary explanations men hardly ever are absolutely certain about their biological fatherhood therefore they must seek various sources of information to subjectively establish whether they are the genetic fathers of the children they raise. Apicella and Marlowe (2004) showed that fathers who perceived greater similarity between their children and themselves were willing to invest more resources (e.g., time, money, care) in their offspring presumably because the perceived resemblance indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(21 reference statements)
2
7
0
Order By: Relevance
“…The study confirmed what has been frequently noted in the psychological literature (e.g. Alexander, 1974; Burch & Gallup, 2000; Dolinska, 2013a; Platek et al, 2002) as to the association between physical resemblance of a man to a child born to his partner and certainty of that man that he is the child’s biological father. The results of the experiment presented above are consistent with this, while it should be emphasized that both technical and ethical considerations prevented fathers from being asked whether they were, in fact, the biological parents of children they were raising.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study confirmed what has been frequently noted in the psychological literature (e.g. Alexander, 1974; Burch & Gallup, 2000; Dolinska, 2013a; Platek et al, 2002) as to the association between physical resemblance of a man to a child born to his partner and certainty of that man that he is the child’s biological father. The results of the experiment presented above are consistent with this, while it should be emphasized that both technical and ethical considerations prevented fathers from being asked whether they were, in fact, the biological parents of children they were raising.…”
Section: Discussionsupporting
confidence: 89%
“…This would obviously mean that the man receives information indicating that he is not the biological father of the child, who is entirely dissimilar to both him and its mother. In a very simple experiment it was demonstrated that people to whom such hypothetical situations were described in which the child is not similar to the father are convinced to a greater degree that the man is the father of the child if that child is similar (vs. dissimilar) to its mother (Dolinska, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…According to the principle of biological discrimination, parents tend to exhibit selective attachment toward their biological kin (Daly and Wilson, 1980;Flinn, 1988). Based on this principle, the study of stepfamilies has shown that stepparents tend to feel differently toward their stepchildren compared to their own children (Coleman and Ganong, 1990;Flinn, 1988) and that stepfamily members are likely to be biased in favor of members who share a biological connection (Archer, 2013;Dolinska, 2013;Jensen and Howard, 2015). Similarly, evolutionary psychology explains the tendency of individual to prefer genetically close others (Nicholson, 2008;Nicholson and White, 2006).…”
Section: Proposition Developmentmentioning
confidence: 99%
“…Second, children who resemble their parents can often expect a higher quality of parental care (Alvergne et al, 2009;Apicella & Marlowe, 2004;Platek, Burch, Panyavin, Wasserman, & Gallup Jr., 2002). The link between resemblance to fathers and increased paternal investment has been repeatedly evidenced (Alvergne, Faurie, & Raymond, 2010;Apicella & Marlowe, 2004;Dolinska, 2013), and surprisingly, mothers have been found to provide care dependent on resemblance as well (Dolinska, 2013;Heijkoop et al, 2009). There is some indication that fathers may base parental investment more on physical resemblance, whereas mothers may base it more on personality resemblance (Heijkoop et al, 2009).…”
Section: Introductionmentioning
confidence: 99%